How city attractiveness and population growth created unaffordable housing in Greater Sydney - Ríos-Ocampo, Juan Pablo; Gary, Michael Shayne (Frontiers in Sustainability, 2025)
Cities worldwide face housing pressure due to rapid population growth exceeding the housing supply. Despite efforts to increase housing supply, housing affordability continues to decline. Understanding policymakers' perceptions of the housing sector in urban planning is critical to guaranteeing housing opportunities for everyone. We examine the complexities of housing affordability in the urban planning process by analyzing three urban planning reports in Greater Sydney. We use an existing dataset for Greater Sydney urban planning reports and causal mapping to analyze policymakers' perceptions about the relationships that drive the housing demand, housing supply, and housing prices. The findings highlight the need for a better understanding of the drivers of urban sprawl, the limitations of current supply-side strategies, and alternative solutions to control urban growth and mitigate housing crises in urban areas.